In-hospital Initiation and Up-titration of Guideline-directed Medical Therapies for Heart Failure with Reduced Ejection Fraction - Zachary L Cox; Shuktika Nandkeolyar; Andrew J Johnson; JoAnn Lindenfeld; Aniket S Rali (Cardiac Failure Review)
Implementation of guideline-directed medical therapy for patients with heart failure is suboptimal. The use of guideline-directed medical therapy improves minimally after heart failure hospitalisation, despite this event clearly indicating increased risk of further hospitalisation and death. In-hospital initiation and titration of guideline-directed medical therapies is one potential strategy to fill these gaps in care, both in the acute vulnerable period after hospital discharge and in the long term. The purpose of this article is to review the knowledge gaps in best practices of in-hospital initiation and up-titration of guideline-directed medical therapies, the benefits and risks of in-hospital initiation and post-discharge focused titration of guideline-directed medical therapies, the recent literature evaluating these practices, and propose strategies to apply these principles to the care of patients with heart failure with reduced ejection fraction.